Intravascular imaging and novel techniques to disrupt severely calcified lesions - Khandkar, Chinmay; Patel, Sanjay; Karimi Galougahi, Keyvan (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
Advancing age and co-morbid conditions (e.g., diabetes and chronic kidney disease) predispose to significant coronary calcification, which is present in up to one third of patients with coronary artery disease [1]. During percutaneous coronary intervention, these heavily calcified segments can present significant challenges, portending higher risks of both immediate complications (e.g. flow-limiting stent edge dissection) and long-term unfavourable events (e.g. in-stent restenosis (ISR), stent thrombosis, and myocardial infarction) compared with non-calcified lesions. Adjunctive techniques such as rotational atherectomy (RA) and recently intravascular lithotripsy (IVL), used in conjunction with imaging technologies such as intravascular ultrasound (IVUS) and optical computed tomography (OCT), are often necessary in treating heavily calcified lesions.